Sustainable disclosures of polish banks – text mining analysis - Białek-Szkudlarek, Martyna (Journal of Finance and Financial Law, 2025)
The purpose of the article. Sustainability development issues, particularly Environmental, Social, and Governance (ESG) factors, are becoming increasingly relevant in corporate reporting, driven by rising environmental awareness and regulatory requirements. The aim of the study is the evaluation of ESG disclosures of selected Polish banks. The aim of the paper fills a gap in the Polish academic literature in economics and finance by analyzing the volume and size of non-financial ESG disclosures through computer text mining techniques. Methodology. This study applies text mining techniques to evaluate the ESG volume and size from 107 financial reports issued by Polish banks between 2006 and 2023. For this purpose, selected tools for computer-based analysis of textual data (text mining) are used. The primary methods include the emotional attitude (sentiment), analysis of the number of words regarding ESG, and analysis of the readability of ESG volume and size contained in company reports. Results of the research. The study reveals that ESG excerpts are more neutral or less optimistic compared to integrated reports, which tend to have a more positive tone. Additionally, sustainability disclosures are written in a complex language, and the volume of these reports has been increasing over time, likely due to new regulations and growing awareness of sustainability issues. The study focuses on Polish banks but suggests expanding future research to other sectors.